Atividade biológica e caracterização de compostos presentes nas folhas e cascas de Cordiera sessilis (Vell.) Kuntze - Ferreira, Alanna Evellin Alves (2018)
Cordiera sessilis, popularly known as "marmelinho do cerrado" is a species native to the Cerrado. According to popular knowledge, its leaves are used in the form of plasters or baths in order to treat conditions on the skin. The leaves and barks of C. sessilis were selected in this work for chemical and biological studies. Ethanolic extracts were obtained from the barks and leaves, after which a liquid partition was performed with the solvent sequence: hexane, dichloromethane, ethyl acetate and n-butanol. The ethanolic extract, fractions and hydrometanic residue were submitted to the tests of antibacterial and antifungal activities, enzymatic inhibition and peroxyl radical sequestration capacity. The hexane fraction of the barks showed promising antibacterial activity against the oral aerobic Streptococcus mitis (MIC 200 μg mL-1) and was selected for column fractionation. From this fraction it was possible to identify, with of GC-MS and NMR, presence of the following compounds: campesterol (2), stigmasterol (3), sitosterol (4), palmitic acid (1), stearic acid (6), behenic acid (7), lignoceric acid (8), methyl 14-methyl pentadecanoate (5), ethyl palmitate (9) and ethyl linoleate (10). The ethyl acetate fraction of the barks showed promising antibacterial activity against oral anaerobic Fusobaterium nucleatum (MIC 200 μg mL-1), antifungal against yeasts Candida albicans (MIC 93,75 μg mL-1) and Candida tropicalis (MIC 93,75 μg mL-1), excellent peroxyl radical sequestration capacity (2415,5 ± 157,8 μmol Trolox eq g-1) and inhibition of lipase enzyme (98,4 ± 2,1%), so was selected for fractionation and identification of compounds. The ethyl acetate fraction of the C. sessilis barks showed the presence of the following compounds, with HPLC-MS/MS: geniposidic acid (11), coumariloylquinic acid (12), caffeoylquinic acid methyl ester (13), lyoniresinol glycopiranoside (14) and dicaffeoylquinic acid (15).